Beginning Windows Phone 7 Development - Lee, Henry; Chuvyrov, Eugene (Apress : Imprint: Apress, 2011)
Microsoft's Windows Phone 7 handsets have injected a new vibrancy into the smartphone marketplace and provided bold new opportunities for the Microsoft development community. Now in its second edition, Beginning Windows Phone 7 Development has been written to help you identify those opportunities and to learn the skills you'll need to harness them. It covers the very latest developments in the field, including the extended APIs offered in Microsoft's automatic platform update, so you'll have timely, accurate information at your fingertips. Beginning Windows Phone 7 Development, Second Edition starts with the basics, walking you through the process of downloading and setting up the right development tools, including Visual Studio, Expression Blend, Silverlight SDK, and Windows Phone SDK. It then takes you step-by-step though the development process as you build and deploy a working application, complete with a sophisticated user interface. Finally, you'll receive step-by-step instructions on selling your applications through the Windows Phone Marketplace.